Christian-Muslim Relations - Thomas, D. (The History of Christian-Muslim Relations, 2011)
Christian-Muslim Relations, a Bibliographical History 3 (CMR3) is the third part of a general history of relations between the faiths. Covering the period from 1050 to 1200, it comprises a series of introductory essays, together with the main body of more than one hundred detailed entries on all the works by Christians and Muslims about and against one another that are known from this period. These entries provide biographical details of the authors where known, descriptions and assessments of the works themselves, and complete accounts of manuscripts, editions, translations and studies. The result of collaboration between leading scholars in the field, CMR3 is an indispensable basis for research in all elements of the history of Christian-Muslim relations.